Integrasi Pendidikan Islam Multikultural dalam Sistem Sosial Pesantren Hidayatullah Bengkulu dan Implikasinya terhadap Pelestarian Budaya Lokal - Yupande, Putra; Rendi, Rendi; Dedek, Rahmad; Asiyah, Asiyah (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – Hidayatullah Boarding School in Bengkulu integrates multicultural Islamic education to address globalization challenges and preserve local culture. This study examines the incorporation of multicultural values into its curriculum and their impact on local traditions.Method – This qualitative case study involves school leaders, teachers, students, and community figures, selected for their roles in implementing multicultural education. The selection process aimed for diverse representation, though further refinement could provide a more comprehensive understanding. Findings – The school combines Islamic teachings with local traditions, such as regional dance, handicrafts, and the Tabot festival, to promote cultural awareness. While students actively engage in cultural activities, the study’s limitations include focusing on one institution and a small sample size. Future research should include multiple schools and use mixed methods for broader applicability. Research Implications – The integration of multicultural values through local cultural practices strengthens students' connection to their heritage, fostering inclusivity and tolerance. The study promotes respect for cultural diversity and appreciation for local traditions amidst globalizations.